Impact of Plurilingualism on Learning Quality in Evening (Shift) Schools - Luka, Ineta; Pigozne, Tamara; Surikova, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This paper presents the main findings of the second stage of the Asia-Europe Meeting (ASEM) Lifelong Learning study (2011-2014) on identification of good practices that facilitate adult learning (aged 18-24) engagement in second chance education in evening (shift) schools. It analyses students’ perceptions of plurilingual learning processes and the impact of people’s plurilingualism on their learning. The methodology of early school leavers’ learning in working life research was used applying combined phenomenological semi-structured and narrative interviews. 116 people (72 early school leavers and 44 second chance education teachers) representing all geographical regions of Latvia were addressed. The study identifies the differences between learning of bilingual and plurilingual people in formal and informal learning environments and describes the impact of plurilingualism on the learning quality.